Isu Kritis Pembelajaran Anak Sekolah Dasar - Widiastuti, Widiastuti; Linora, Linora; Hendrizal, Hendrizal (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to determine critical issues in elementary school children's learning. Several factors that could be the cause of not maximizing student achievement or enthusiasm for elementary school students' learning include: too abstract teaching materials,less interesting delivery by an educator, less active students, less optimal media used as teaching materials, or less precise models. learning.This research uses a qualitative approach. The results of the research show that elementary school children's learning includes: 1)Interactive and fun learning, effective learning is characterized by an ongoing teaching and learning process that is able to teach students and obtain satisfactory learning achievements 2) Linking material with everyday life, paying attention to student activities in learning that is able to train students to relate learning concepts to real life situations 3) Using interactive media technology, the low quality of educational facilities and infrastructure can be caused by various factors, such as hampered distribution of funds, misuse of school funds, poor maintenance of facilities and infrastructure,supervision of school officials who are indifferent to facilities and infrastructure, and other factors,4)providing rewards. Rewards in learning are that students will receive awards after learning well and following the rules given by the teacher and school.